The Role of Women in the Spiritual Development of Society - Khayrullayeva Maftuna (Zien Journals, 2023)
Based on contemporary science and core national spiritual principles, our nation is implementing extensive reforms aimed at reviving society, enhancing its spiritual realm, and modernizing it. The efficiency of the socially significant spiritual elements of society is thought to be ensured in this process by the essential role that women play. This subject is extensively covered in the essay.
Keywords: spirituality; spiritual factors; civil society; globalization; spiritual immunity